Overview of withdrawal syndrome mechanisms in different substance abuse addictions: Neuronal circuits and transmitters - Hamidreza Famitafreshi; Morteza Karimian (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Substance abuse is one of the major concerns of human societies. Many problems exist for controlling drug abuse that profoundly influences treatment. One of the most important and prevalent problems is Withdrawal Syndrome (WS). The WS describes a host of unpleasant symptoms that develop in the withdrawal period. WS should be suppressed in the withdrawal period because in the presence of WS dependence on drugs will continue. Using the drug to which one is addicted is the most effective way to suppress the withdrawal syndrome, which is why many users relapse after a period of abstinence. The purpose of this review article is to describe the basic brain mechanisms that are responsible for the emergence of WS that cannot be tolerated in the abstinence period. This may be helpful for a better understanding of the nature of WS in the withdrawal period for implementing the best approach with new insights for highlighting new horizons for future goal-directed studies. The important topics in this regard are non-related brain areas based on recent studies that have been proposed. They have included the rewarding center, endogenous cannabinoid system, corticotropin-releasing factor, locus coeruleus, and orexin system. According to the above facts, this syndrome arises with different mechanisms, and a multi-approach treatment toward this syndrome is required.